Preeclampsia and uteroplacental acute atherosis: Immune and inflammatory factors - Staff, A; Johnsen, G; Dechend, R; Redman, C (Elsevier, 2014)
Acute atherosis (Aa) affects uteroplacental spiral arteries in 20-40% of cases of preeclampsia. Its hallmark is lipid-filled, CD68-positive foam cells. It usually develops in the decidua (the pregnancy endometrium) at the distal ends of arteries that are often unremodelled in their proximal segments. Aa resembles the early stages of atherosclerosis, which becomes symptomatic in the middle-aged and elderly, in contrast to the young age of pregnant women with Aa. Although the mechanisms of Aa are largely unknown, they are likely to resemble those of early atherosclerosis, which is an inflammatory lesion of the arterial wall. However, Aa is likely to have added pregnancy-specific features. Because it also occurs in normotensive pregnancies, complicated by foetal growth restriction, diabetes mellitus or autoimmune disease or even without any complications, we suggest that Aa is the final manifestation of several inflammatory processes. We revisit an old proposition that immunological incompatibility between mother and foetus may sometimes induce Aa. We propose that excessive inflammatory activation, of other aetiologies, primarily in the decidua basalis, may explain the different ways in which Aa occurs. We speculate that the subset of women who develop these lesions may be at an increased risk of atherosclerotic arterial disease later in life. We hypothesise that use of anti-atherogenic statins during established preeclampsia may ameliorate Aa, improve uteroplacental perfusion and enhance pregnancy outcome. © 2013.